TO ASSESS THE EFFECT OF SMOKING, PASSIVE SMOKING & SOCIOECONOMIC STATUS ON THE DEVELOPMENT OF TB IN PATIENTS OF DHQ HOSPITAL FSD - Hira Gul; Iqra Fatima (Journal of University Medical & Dental College, 2013)
ABSTRACT Objective of the study was to assess the effect of smoking, passive smoking and socioeconomic status on the development of active pulmonary tuberculosis (PTB) This is a Descriptive cross sectional study, which was conducted at DHQ hospital Faisalabad in May, 2012. Thirty patients of tuberculosis from DHQ hospital were included in the study by filling of questionnaire. Out of these, 70% were smokers and 20% were passive smokers and only 10% were nonsmokers. Most of the smokers had been smoking for more than 10 years. 70% of the patients were belonging to low socioeconomic status. 23.33% had a view that smoking is a causative factor in their TB and 76.66% were against it. In conclusion, exposure to tobacco smoke, either active or passive, was associated with an increased risk of developing pulmonary tuberculosis immediately following infection. This is an association of great concern requiring health education programs and anti-tobacco medical advice.